If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-4 + -2y) + 3y = -1 Remove parenthesis around (-4 + -2y) -4 + -2y + 3y = -1 Combine like terms: -2y + 3y = 1y -4 + 1y = -1 Solving -4 + 1y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1y = -1 + 4 Combine like terms: -4 + 4 = 0 0 + 1y = -1 + 4 1y = -1 + 4 Combine like terms: -1 + 4 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 25*ln(x)+19*ln(x)+13*ln(x)= | | 2x-9x+4x=7 | | x-3=2+3y | | ln(x+5)=0.2 | | (X+4)+(2x-3)= | | 0.2=ln(x+5) | | (X+4)+(2x+3)= | | x^3+6x+8=0 | | 7+5x=-13+7x | | -w-4/2=0 | | 3(x-7)+3x=-3 | | (4-2y)+3y=-1 | | 2(x-6)-3x=-2 | | -56x+45z^2-45=0 | | 5(t-4)+5t=5(2t+4)-11 | | 6(k-7)=9(k) | | 0.4(x+50)+0.8=56 | | A=1/3zks | | 4+6n-3=4n+17-2n | | 6x^2=54x+36-0 | | 7l^2-274l-440=0 | | 7=20-16x^2 | | 37/6= | | F(x)=3x^2+5x-6 | | 18(t-3)+3t=7(3t+3)-10 | | V-b=5 | | 0.30x+0.05(12-x)=0.10(21) | | 0.5x-1.1=3.6x+2.3 | | 72y=180 | | y+72y=180 | | 0=1296-.36x^2 | | 2(x+6)=24 |